TRANSAKSI E-COMMERCE DALAM PENERAPAN PP NO. 23 TAHUN 2018 PADA KOPERASI SERBA USAHA DAYA GUNA MANDIRI MALANG - Sukarno Himawan Wibisono; Poppy Indrihastuti; Chindi Valen Renati (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2021)
This study aims to determined the application of Government Regulation No. 23 of 2018 concerning MSME Income Tax in e-commerce transactions at the Multipurpose Multipurpose Cooperative Mandiri Mandiri Malang. This study used a descriptive method through interviews, observation and documentation. The results showed that e-commerce transactions have been effective, when viewed from the online sales turnover (e-commerce) in one year, it was in accordance with Government Regulation No. 23 of 2018. It means that the income of the cooperative in one period was still below Rp. 4,800,000,000 and subject to a 0.5% rate, therefore the turnover of online sales (e-commerce) is Rp. 170,255,000 in one period.